Treatment of Irritable Bowel Syndrome Somatic Comorbidities by Osteopathic Approach (Nigerian Journal of Health Sciences, 2023)
Irritable bowel syndrome (IBS) is a chronic continuous or intermittent gastrointestinal tract dysfunction encountered by the health professionals. IBS patients are afflicted with intestinal and extraintestinal somatic morbidities. The aim of the present case study was to explore the effect of osteopathic treatment (OT) on somatic comorbidities in IBS patients. The author reported a 43‑year‑old female case who presented with a headache, abdominal pain, pain in the one‑half of the body, lower back pain, increased the frequency of stool passage in a day, with alternating diarrhea or constipation, bloating; with few occasions of nausea and vomiting. The patient had history of 3‑year‑old hysterectomy and with no other relevant medical history. On endoscopic, colonoscopy, and blood investigations, no abnormality was detected. In this case, the osteopathic diagnosis was made as visceral somatic dysfunction and the OT made the remarkable difference in the patient symptoms as assessed by bowel symptom scale.